Throwing it out there: Grip on multidimensional performance characteristics of judoka - a systematic review - Schoof, S.; Sliedrecht, F.; Elferink-Gemser, M. T. (International Journal of Sports Science & Coaching, 2024)
Judo is a dynamic and complex sport, and therefore talent programs may benefit from a multidimensional approach to identify clear and reliable performance characteristics in order to monitor and train athletes. However, from both a practical and theoretical point of view, understanding on this topic is limited. This systematic review therefore aimed to (1) identify which multidimensional performance characteristics can discriminate between different performance levels of judoka and (2) find the gaps in literature. To categorize the findings the Groningen Sport Talent Model (GSTM) was applied. A systematic search of MEDLINE, PsycINFO, PubMed, and Web of Science was performed following the PRISMA guidelines. In total 23 studies with good to excellent methodological quality were included. All performance characteristics of the GSTM (anthropometrical, physiological, technical, tactical, and psychological) were represented in the included studies. There is strong evidence to suggest that a broad set of physiological characteristics is needed to manage the demands of judo combats. Additionally, there is strong evidence that performance characteristics related to grip fighting discriminate between judoka of different performance levels and higher performance level judoka are characterized by the ability to throw their opponent and to variate in technique. The findings of this review can be used as a basis for talent development and identification in judo, and to optimize training programs. Future research should focus on increasing the understanding of psychological characteristics of judoka and the multidimensional talent trajectory by conducting longitudinal studies.